Comparative Aging and Qualitative Theorizing - Cook, Ian G.; Halsall, Jamie; Powell, Jason L. (Qualitative Sociology Review, 2021)
The principal aim of this argument is to analyze the swift expansion in the proportion of older people across the globe, and to highlight the main social and economic forces causing this through methodological challenges especially through the lens of qualitative methodology. We recognize the enormity of the task. Drawing from a range of qualitative research studies provides enriched meanings about aging identity that can be used to shed light on how aging is experienced in equal to how it has been defined in macro or populational terms. Balancing micro and macro levels of understanding is key to open up broader level of explaining what it means to be an older person in different cultures Whilst this is a noble aim, there is no doubt that the rapid increase in population aging across the globe is signalling the most astonishing populational changes in the history of humankind that qualitative levels of understanding are uniquely placed to balance the huge figures in describing complex demography in that qualitative methodology unravels the facts and instead reveals the narratives, meanings and identity formation of research subjects; whereas statistical research has pre-dominantly made its findings looking at people as research objects or as a ‘number’ (Gruber and Wise 2004). The balance is key but this paper explores the issue of comparative aging underpinned by what Powell and Cook (2001) call ‘qualitative theorising’ in making sense of statistical and experiential aging.